Molecular Markers Associated to Two Non-allelic Genic Male Sterility Genes in Peppers (Capsicum annuum L.) - Naresh, Ponnam; Lin, Shih-wen; Lin, Chen-yu; Wang, Yen-wei; Schafleitner, Roland; Kilian, Andrzej; Kumar, Sanjeet (Frontiers in Plant Science, 2018)
Male sterility is of high importance in hybrid seed production of hot and sweet peppers. Genic (or nuclear) male sterility (GMS) is a simply inherited (usually monogenic recessive) and highly stable trait. However, one major disadvantage of using GMS is 1:1 segregation of male sterile to male fertile plants in every subsequent generation. Molecular markers tightly linked to genic male sterility (ms) genes would facilitate an efficient and rapid transfer of ms genes into different genetic backgrounds through marker-assisted backcrossing. The two non-allelic genic male sterility genes ms3 and msw in hot and sweet pepper backgrounds, respectively, are monogenic recessive. Genotyping by sequencing (GBS) in an F2 population segregating for ms3 gene in hot pepper and in an F6 inbred near-isogenic line (NIL) population segregating for msw gene in sweet pepper yielded 9,713 and 7,453 single nucleotide polymorphism markers, respectively. Four candidate SNPs co-segregating with ms3 gene and one co-segregating with msw gene were identified by bulk segregant analysis and physically mapped to chromosomes 1 and 5, respectively. In hot pepper, two markers [HPGMS2 (CAPS) and HPGMS3 (dCAPS)] located 3.83 cM away from the ms3 gene and in sweet pepper the dCAPS marker SPGMS1 co-segregated (completely linked) with the msw gene were developed. These markers will increase the efficacy of the male sterility genes for pepper breeding, as they can be useful in developing the genic male sterile lines in parental inbred lines of commercial hybrids through marker-assisted backcrossing, hybrid seed production, and genetic purity testing of hybrid seeds.